Thymus-derived macrophages in long-term culture: release of IL-1, stimulation of MLR and expression of tumoricidal activity. - Gallily, R (1985)
The present report examines the behaviour of a slowly proliferating pure population of thymus-derived macrophages in long-term culture, regarding their ability to secrete interleukin-1 (IL-1) and prostaglandin E2 (PGE2), to stimulate a mixed leucocyte reaction (MLR) and to lyse tumour cells in vitro. Following stimulation with LPS, high levels of IL-1 were released to the medium. IL-1 release was significantly augmented by the addition of indomethacin during stimulation. Thymus-derived macrophages constitutively secreted significant levels of PGE2. These cells served as excellent stimulators in a one-way MLR, substantiating the claim that pure populations of macrophages effectively stimulate an allogeneic response in vitro. Thymus-derived macrophages showed tumoricidal activity following activation with either high concentrations of LPS or suboptimal concentrations of LPS and T-cell lymphokine. These findings portray a close interrelationship and reciprocal regulation between thymus-derived macrophages and T lymphocytes.